Bidirectional superior cavopulmonary anastomosis: how young is too young?. Issue 1 (January 1996) - Slavik, Z.; Lamb, R. K.; Webber, S. A.; Devlin, A. M.; Keeton, B. R.; Monro, J. L.; Salmon, A. P.
Abstract : OBJECTIVE–To define the lowest age at which the bidirectional superior cavopulmonary anastomosis can safely be used in infants with complex congenital heart defects. DESIGN–A retrospective analysis of clinical, echocardiographic, haemodynamic, and angiographic data in four consecutive patients undergoing bidirectional superior cavopulmonary anastomosis below the age of 2 months. PATIENTS–Between November 1990 and September 1993, four infants less than 8 weeks of age (3, 4, 6, and 7 weeks) underwent bidirectional superior cavopulmonary anastomosis as a primary palliation for complex heart disease. The indication for early surgical intervention was progression of cyanosis (n = 3) and high pulmonary blood flow causing heart failure (n = 1). In two infants with tricuspid atresia, surgery was performed through a right thoracotomy without the use of cardiopulmonary bypass. In one infant with double inlet left ventricle and discordant ventriculoarterial connection, cavopulmonary anastomosis was combined with an arterial switch procedure. The final infant had double inlet left ventricle with pulmonary atresia; the central pulmonary arteries were virtually discontinuous and each branch was supplied by a separate arterial duct. The central pulmonary arteries were reconstructed using the subaortic innominate vein. Temporary prostacyclin infusion was used in three patients in the immediate postoperative period. RESULTS–Early postoperative extubation (5, 7, and 48 h) was successful in three patients. The youngest child required ligation of the ductus arteriosus four days later because of severe upper body oedema. The postoperative course was complicated by prolonged effusions in two patients. All were alive and well 14-48 months postoperatively, with satisfactory systemic saturations (80-87%) and haemodynamic indices. CONCLUSIONS–This limited experience challenges the widely held belief that the bidirectional superior cavopulmonary anastomosis cannot be used as a primary palliation for complex heart disease in early infancy. A wider experience is required to determine the safety and indications for this approach.